Pengaruh Audit Fee, Audit Tenure, dan Audit Delay Terhadap Kualitas Audit dengan Komite Audit Sebagai Variabel Moderasi - Valentina Putri Fauzi; Hero Priono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research related to audit quality aims to prevent violations and misstatements in financial reports. Audit quality can help to maintain the level of confidence of financial report users in the validity and accuracy of financial reports that have been audited and published by the auditor. This research uses descriptive quantitative research methods because it presents an overview of the relationships and objectives of the variables studied. The results of this research state that audit fees contribute to audit quality in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2020 - 2022 period.